Avaliação Diagnóstica em Intervenção Precoce - Franco, Vítor (2012)
The development of early intervention in Portugal and in the region of Alentejo, where it was installed a locally based network, has made evident the need to clarify the diagnosis and assessment practices, and it importance for eligibility and as a guide to intervention practices. Will be presented here the results obtained in the experimental application of a portuguese version of ODAT (GAT, 2004, 2008) for a sample of 1169 children, pointing to the high potential of this tool for the work of professional teams of the National Early Childhood Intervention System.